Aztec shape metamaterial-based bandpass filter for C, X and Ku-band applications. (January 2019) - Alam, M J; Ahamed, E; Faruque, M R I; Hossain, M J; Islam, M T
Abstract: The paper presents the structure of an Aztec shape metamaterial unit cell that is suitable for a triple band of microwave frequencies. A comparative analysis has been made on the performance of the unit cell with several array structures. A low profile dielectric substrate FR-4 is used on which the design is made. The proposed structure operates at 6.3, 8.9, 11.91, and 16.42 GHz respectively. The double negative characteristics can also be found at X and Ku-band separately. Having a compact design, double-negative characteristics and the proposed metamaterial has potential to be used for triple band applications, especially for C, X and Ku-band.